Title: Enhancing Surface roughness and Wettability of Commercial Pure Titanium Implants with Electrospun PCL/Chitosan/Cinnamon composite - Khadija Sahib Hasen 1*, Ghassan Abdul-Hamid Naji 2 , Akram R. Jabur3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
To enhance the properties of titanium for implant applications,PCL/Chitosan/cinnamon watery extract  composite  were deposited on commercially pure titanium specimens using electro spinning technique . Water contact angle and surface roughness(Ra) tests were conducted, revealing significantly increased Wettability and(Ra)  in the coated samples, a finding supported by statistical analysis. This increased surface roughness   will potentially improve the Wettability properties of titanium which has demonstrated the significant impact of these surface characteristics on cellular responses to biomaterials.